CLONINIG AND EXPRESSION OF CAG PATHOGENICITY ISLAND ANTIGENS FOR THE PRODUCTION OF VACCINE AGAINST HELICOBACTER PYLORI, THE RISK FACTOR FOR GASTRIC CANCER - BASSAM SHAKER MAHMOOD; SELVAM ARJUNAN; RADHAKRISHNAN SENTHILKUMAR (International Journal of Pharma and Bio Sciences, 2014)
In the present study we cloned and characterized the cagN gene from Helicobacter pylori to develop an antigen for the protective immunity against gastric helicobacter. The cagN gene from Helicobacter pylori was amplified using specific primers and cloned in pTZ57R/T and transformed into DH5α cells. The plasmid DNA obtained was then confirmed by restriction digestion and sequence analysis. The sequence was found to be 99% similar to that obtained in GenBank. The sequence of cagN gene amplified by the specific primer is closely matched (99%) with a Helicobacter pylori strains. The gene restricted from the cloning vector was ligated to expression vector. Transformation was confirmed with plasmid extraction and followed by restriction digestion. IPTG was used as an inducer for the expression of cagN protein and the protein was successfully isolated and quantified. The quantified protein was subjected to SDS PAGE to evaluate the expression of that protein. After staining with coomassie staining a specific band was observed at an approximate molecular weight of 20 KDa. The discovery of a protective antigen of Helicobacter pylori offers further hope that an effective vaccine can be produced for human usage